Energy Efficient Smart Home Based on Solar Panels - Siswanto, Meilana; Prasetyo, Dafit Ari (Food and Agricultural Sciences : Polije Proceedings Series, 2020)
Renewable energy has been and is still a hot issue today, especially in the era of the industrial revolution 4.0, where everything will be connected to the internet or the internet of things. The application of Internet of Things (IoT) to a system will require non-stop electrical energy to ensure the system can work properly. Various efforts have been made to find alternative energy sources that are sustainable and environmentally friendly to overcome the energy crisis that will hit the world. Solar energy is one of the renewable energies that is in great demand and is predicted to experience significant development compared to other renewable energy sources. Apart from being environmentally friendly, solar energy is also easy to maintain, install and is a sustainable source of energy. This paper will discuss the design and application of solar panels for a smart home to save electricity consumption. The saving percentage of electrical energy consumption after installing solar panels 1440 Wp in ideal conditions regardless of weather and other factors is between 54.91% - 60.84%.